Analisis Tokoh Dan Penokohan Dongeng Sebagai Bahan Ajar Menceritakan Tokoh-Tokoh Pada Cerita Fiksi - Sulistiawati; Widjojoko; Deni Wardana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
In the Indonesian lesson, the purpose of speaking skills is so that students are able to communicate orally and in writing. One of the goals with students is able to tell orally or in writing the content contained in the text that has been read. This study is intended to analyze the characters and characters in a fairy tale book entitled